UPAYA MENINGKATKAN PEMAHAMAN KONSEP PENDIDIKAN KEWARGANEGARAAN (PKN) DENGAN MEDIA CHARTA DI KELAS IV SEKOLAH DASAR - ., Epayanti; Usman, Andi; Wibowo, Deki (Jurnal Pendidikan Dasar, 2015)
Abstract: This research highlights the problem of applying Charta Mediato improve students concept understanding on the material of governmentsystem in fourth grade at Public Elementary School 02MenukungAcademic Year 2012/2013. The type of research used wasClassroom Action Research. The subjects of the study are the fourth gradestudents of Public Elementary School 02 Menukung in the even semesterof the Academic Year 2012/2013 Sub District Menukung, MelawiRegency, which amounted to 22 people, consisting of 9 women and 13men. Data collection techniques were conducted using observation andtest techniques. The average test scores achieved by students on the precycle is 55.45, while on the first cycle it reached 65.45 and achieved78.18 on the second cycle. To conclude, the student learning resultshowed an increase from cycle I to cycle II. The implementation of RPPon cycle I with average percentage of implementation that includes 3activities (preliminary, core, closing) is equal to 68,42%. The details arepreliminary activity of 68.75%, and the core of 66.67% whiletheclosingof 75.00%. This figure increased on cycle II, with the averagepercentage of learning implementation rose to 80.55%, with details of75.00% in preliminary activities, 80.00% in core and 100.00% inclosing.Keywords: conceptual understanding, media chartaAbstrak: Penelitian ini menyoroti masalah penerapan media charta untukmeningkatkan pemahaman konsep siswa pada materi sistem pemerintahandi kelas IV SDN 02 Menukung Tahun Pelajaran 2012/2013. Jenispenelitian adalah penelitian tindakan kelas. Subjek penelitian adalahsiswa kelas IV SDN 02 Menukung semester genap Tahun Pelajaran2012/2013 Kecamatan Menukung Kabupaten Melawi, yang berjumlah 22orang, terdiri 9 perempuan dan 13 laki-laki. Teknik pengumpulan datadilakukan dengan menggunakan teknik observasi dan tes. Rata-rata skortes yang diperoleh siswa pada pra siklus sebesar 55,45, siklus I sebesar65,45 sedangkan pada siklus II sebesar 78,18. Ini berarti dari siklus I kesiklus II hasil belajar siswa mengalami peningkatan. Keterlaksanaan RPPpada siklus I rata-rata persentase pelaksaanaan yang meliputi 3 kegiatan(pendahuluan, inti, penutup) adalah sebesar 68,42%. Rinciannya adalahÂ kegiatan pendahuluan terlaksana sebesar 68,75%, inti 66,67% danpenutup 75,00%. Angka ini meningkat pada siklus II, rata-rata persentasepelaksanaan pembelajaran naik menjadi 80,55%, dengan rincian kegiatanpendahuluan 75,00%, inti 80,00% dan penutup 100,00%.Kata kunci: pemahaman konsep, media charta